THE RELATIONSHIP BETWEEN READING COMPREHENSION AND VOCABULARY IN EARLY STUDENTS - Khusnobod Abdiraimova Samat kizi (Western European Studies, 2025)
This article provides a scientific analysis of the interrelationship between reading comprehension skills and vocabulary knowledge among young learners. The study demonstrates that during the process of reading, the level of comprehension directly influences learners’ lexical repertoire, while the richness of vocabulary, in turn, plays a crucial role in enhancing the quality of reading comprehension. It is revealed that students with insufficient vocabulary face difficulties in achieving full understanding of a text, whereas those with a broader vocabulary demonstrate higher reading efficiency. The article also emphasizes the significance of employing various methods and strategies to develop reading comprehension, particularly highlighting the role of vocabulary-enriching activities. This research carries practical importance for improving literacy in primary education, fostering learners’ language competence, and contributing to their cognitive development.
Keywords: reading comprehension; vocabulary; young learners